Постправда і народний наратив: семантико-прагматичні стратегії трансформації фейків у меми в українському суспільстві в умовах війни - Скорофатова, Анна (Slavia Orientalis, 2026)
This article explores Ukrainian memes that have emerged since the beginning of the full-scale Russian-Ukrainian war, all through the lens of post-truth and information warfare. Meme culture is seen as a type of digital folklore that turns false narratives into powerful tools for satire, psychological relief, and building national identity. The study aims to explore the ways humour, exaggeration, bizarre imagery, and post-ironic elements are used to reshape fake news. The research is based on a collection of over 4,500 multimodal memes gathered from various social media platforms. To analyze this, the study employs semiotic, discourse, and content analysis methods. The findings reveal three main categories of “meme-based pseudo-facts”: informational fakes, visual fakes, and ironic fakes, each serving purposes such as emotional release, mocking the enemy, normalizing life during wartime, and creating grassroots heroes. The study pays special attention to dark humor as a way to cope with the trauma of war. The research highlights what makes the Ukrainian case unique: a strong presence of post-irony, a high level of multimodal blending, and a focus on emotional resilience. The conclusions emphasize how memes play a crucial role as tools for information resistance, social mobilization, and psychological strength in the face of hybrid warfare.